Endemic Contagious Agalactia in Sheep and Goats: Clinical Evaluation, Treatment and Vaccination - Macun, Hasan Ceyhun; Ocal, Naci; Karahan, Murat; Yagci, Bugrahan Bekir; Kalender, Hakan; Kalin, Recep (Medwell Online, 2010)
In this study, it aimed to evaluate clinical signs of Contagious Agalactia (CA) that had been affecting small ruminants in Kirikkale Province for 1.5 years and to intervene with this endemic CA by administration of enrofloxacin 5 mg kg(-1) for 5 days and a single dose of meloxicam (0.5 mg kg(-1)) to acutely infected animals and by vaccination of the flocks. The study was conducted between July 2007 and December 2008 on a total of 745 animals of 5 different flocks with problems of mastitis, keratoconjunctivitis and arthritis. Clinically determined CA was also confirmed by PCR analysis of milk samples. Arthritis was the most frequently observed clinical sign with a rate of 71.84% in diseased animals. Arthritis was observed either as a single problem or concurrently with mastitis or ocular lesions. The co-existence rate of ocular lesions with mastistis was 2.91% while observing all three lesions concomitantly was the least frequent, 2.91%. Ocular lesions alone was not seen in ewes and goats but co-existed with other signs. Ewes and goats exhibited a higher frequency of mastitis alone with a rate of 45 and 44.83%, respectively compared to other two clinical signs. The treatment protocol mentioned above was successful as the general body condition of the clinically diseased animals was improved and subsequently no incidence of death was observed. Animals gradually recovered from mastititis and conjunctivitis and the severity of keratoconjunctivitis and arthritis was decreased. It also concluded that application of a live CA vaccine twice with a 6 month-interval was quite effective as no case of CA was observed in vaccinated flocks during a 1 year follow-up period.
Keywords: Contagious agalactia; clinical evaluation; enrofloxacin; meloxicam; treatment vaccination